Sistem Manajemen Strategik Dengan Pendekatan Balanced Scorecard Pada Perguruan Tinggi - Kusumawati, Yuli Noor; Tjahjono, Heru Kurnianto (JIK: Jurnal Ilmu Komputer, 2003)
This article addresses strategic management of which a design formula utilizing balanced scorecad approach is applied at higher education institutions. The Yogyakarta Muhammadiyah University is selected as a research subject of balanced scorecard design.Ã‚Â  The application of balance scorecard approach in the private sector, has been popular. On the contrary, studies related to balanced scorecard in the public sectorÃ‚Â  or non-profit organization are still conceptually scarce, especially in formulating the design. ThisÃ‚Â  may technically provide a basis for the research to brigde the scarcity of formulating strategic management design system. Researchers devise the system by means of literature and empiric data explored from observation. Then the research results offer alternatives for higher educations. Eventually, the advantages of the system is expected to enhance of the institutions, so that competitive advantages may be improved.Kata Kunci: Strategic management system, balancedscorecad,Ã‚Â  quality and designÃ‚Â